If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + -3b + 8a + -5b = 0 Reorder the terms: 7a + 8a + -3b + -5b = 0 Combine like terms: 7a + 8a = 15a 15a + -3b + -5b = 0 Combine like terms: -3b + -5b = -8b 15a + -8b = 0 Solving 15a + -8b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8b' to each side of the equation. 15a + -8b + 8b = 0 + 8b Combine like terms: -8b + 8b = 0 15a + 0 = 0 + 8b 15a = 0 + 8b Remove the zero: 15a = 8b Divide each side by '15'. a = 0.5333333333b Simplifying a = 0.5333333333b
| 10.5+54.5x= | | (x*x)+2x=120 | | 2x^2+9x-45=0 | | -12=2x+4 | | -8x+(-16)=24 | | 5p+7-5p=-7*(p-3) | | 5p+7-5p=7*(p-3) | | 3(3-1)=x | | 96.3=9(m+2.4) | | (4b+5)+(4b-2)= | | -2(3y-4)+6= | | 3(3-1)= | | y-2=-13 | | 7x-36=b | | 1/7x-y=18 | | 8.4(x-3.25)=-25.2 | | 5mn+3nm= | | 114=-16t^2+95t+0 | | 4x+(-4x)+4+2x= | | 60=x+.07x | | x^3+7x^2-64x-448=0 | | 3x^2+(1+2i)x+1-i=0 | | -5/2x=-10 | | 98=7x+35 | | (x^2+9x-5)(x^2+8x-3)=0 | | 7x-36= | | (4x-25)+90=180 | | y+6=-6(x-5) | | -.4(p+22)=34 | | -sqrt(x+10)=-7 | | (10x+2)+90=180 | | -5t^2+50t+5=0 |